2017
DOI: 10.1111/jpn.12652
|View full text |Cite
|
Sign up to set email alerts
|

Influence of sumac (Rhus Coriaria L.) and ginger (Zingiber officinale) on egg yolk fatty acid, cholesterol and blood parameters in laying hens

Abstract: The aim of the study was to evaluate the potential effect of different levels of sumac (Rhus coriaria L.) seed powder and ginger (Zingiber officinale) root powder on egg yolk fatty acid composition, blood/yolk cholesterol in laying hen. A total of 63 (ATAK-S: Domestic Turkish Laying Hens) laying hens (average weight: 1470 g each hen, 25-weeks of age) were assigned to seven treatment diets including sumac seed (S) and ginger root powder (G) at 0 g/kg (control), 10 g/kg (S1), 20 g/kg (S2), and 30 g/kg (S3); 10 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 24 publications
(29 reference statements)
4
15
0
Order By: Relevance
“…While, LDL level decreased significantly, HDL levels increased in the sumac group compared to the control. Gurbuz and Salih (2017) found that supplementation sumac (10,20 and 30g/kg)or ginger power (10,20 and 30 g/kg)in hens diets significantly increased HDL and decreased LDL and cholesterol levels in the blood of hens. On contrary, Sharbati et al (2013) found that the blood total protein of sumac or vit.…”
Section: Blood Constituentsmentioning
confidence: 91%
See 2 more Smart Citations
“…While, LDL level decreased significantly, HDL levels increased in the sumac group compared to the control. Gurbuz and Salih (2017) found that supplementation sumac (10,20 and 30g/kg)or ginger power (10,20 and 30 g/kg)in hens diets significantly increased HDL and decreased LDL and cholesterol levels in the blood of hens. On contrary, Sharbati et al (2013) found that the blood total protein of sumac or vit.…”
Section: Blood Constituentsmentioning
confidence: 91%
“…Onkar et al (2011) revealed that the seeds of sumac are rich in phenolic compounds and the isolated aromatic compounds showed antifungal activity against candida albicans and aspergillus flavus. Gurbuz and Salih (2017) found that contents of chemical composition of sumac seed, total phenolic (2.46%) and total flavonoid (4.81%). The animal experiments have shown that R. coriaria also has caused protection in inner organs.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…This may be explained by the radical-scavenging effect of phenolic compounds and antioxidant components in ginger extract, which reduce lipid oxidation [63] and enhance the function of body organs as partly reflected by decreased the serum activities of ALT and AST, thus improving the production and synthesis of antioxidant enzymes [64]. On the same line, Gurbuz and Salih [65] found that powder of ginger root lowered yolk cholesterol content. The hypocholesterolemic effect of this plant was also recorded in broiler chickens [18].…”
Section: Effect Of Ginger On Meat and Egg Qualitymentioning
confidence: 96%
“…It was thus ascertained that dietary cholesterol, including egg yolk, is harmful to the arteries . Hen breeders even started to select hen lines that produce eggs with low cholesterol or tried to including additives to reduce the cholesterol of shell eggs . This made people (especially including the health conscious) choose only the egg white – albumin – for food and discard the yolk.…”
Section: Introductionmentioning
confidence: 99%